(untitled) (Mongolian Journal of Agricultural Sciences, 2023)
In this study, we aimed to purify antibacterial peptides like bacteriocin from the cell-free supernatant of L.paracasei 1-g isolated from traditional Mongolian Airag. The antibacterial peptide was purified by a sequential purification method via ammonium sulfate precipitation, gel filtration, and ion exchange chromatography on SP-Sepharose and Reversed phase chromatography. The purification exhibited a 25-fold increase compared to the cell-free supernatant. The purified peptide displayed antibacterial activity of 6400 AU/ml at neutral pH against indicator strains. The peptide portrayed high thermal stability sensitivity to proteolytic enzymes. The molecular weight of the peptide was 2056.424 Da as measured by MALDI TOF MS analysis.